2019
DOI: 10.1002/jhet.3638
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis and Antimicrobial Evaluation of New Azolopyrimidines‐Bearing Pyrazole Moiety

Abstract: Sodium salt of 3‐hydroxy‐1‐(1‐aryl‐5‐methylpyrazolyl)propenone derivatives was used as a precursor for synthesis of various fused azolopyrimidine ring systems as pyrazolopyrimidines, triazolopyrimidines, and pyrimidobenzimidazoles following many procedures. The identity of the prepared compounds was elucidated by their spectral data and elemental analyses. The in vitro antimicrobial activity of 13 new compounds was evaluated, and many derivatives showed good to moderate activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…[1][2][3] A literature survey revealed that many heterocyclic derivatives having pyrazole as core structure exhibiting a broad spectrum of approved biological activities such as antiinflammatory, antipyretic, gastric secretion stimulatory, antidepressant, antibacterial, antifilarial agents, HIV-1 non-nucleoside reverse transcriptase inhibitors and dual inhibitors of CCR5/ CXCR4 HIV entry. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] Furthermore, this pharmacophore is occur in several well-known active drugs such as Rimonabant, Celecoxib, Tepoxalin, Viagra, Lonazolac, and Fipronil [18][19][20][21] which are enlisted among the most selling drugs albeit few have been retrieved from the market owing to the side effects. Moreover, the other applications of pyrazole derivatives were also well reported in the fields of fluorescence, agriculture, luminophores, and drug discovery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] A literature survey revealed that many heterocyclic derivatives having pyrazole as core structure exhibiting a broad spectrum of approved biological activities such as antiinflammatory, antipyretic, gastric secretion stimulatory, antidepressant, antibacterial, antifilarial agents, HIV-1 non-nucleoside reverse transcriptase inhibitors and dual inhibitors of CCR5/ CXCR4 HIV entry. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] Furthermore, this pharmacophore is occur in several well-known active drugs such as Rimonabant, Celecoxib, Tepoxalin, Viagra, Lonazolac, and Fipronil [18][19][20][21] which are enlisted among the most selling drugs albeit few have been retrieved from the market owing to the side effects. Moreover, the other applications of pyrazole derivatives were also well reported in the fields of fluorescence, agriculture, luminophores, and drug discovery.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazoles are well recognized class of bioactive drugs in the pharmaceutical industry and privileged core for pharmaceutical targets in the synthetic as well as naturally occurring compounds [1–3] . A literature survey revealed that many heterocyclic derivatives having pyrazole as core structure exhibiting a broad spectrum of approved biological activities such as anti‐inflammatory, antipyretic, gastric secretion stimulatory, antidepressant, antibacterial, antifilarial agents, HIV‐1 non‐nucleoside reverse transcriptase inhibitors and dual inhibitors of CCR5/CXCR4 HIV entry [4–17] . Furthermore, this pharmacophore is occur in several well‐known active drugs such as Rimonabant, Celecoxib, Tepoxalin, Viagra, Lonazolac, and Fipronil [18–21] which are enlisted among the most selling drugs albeit few have been retrieved from the market owing to the side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to their photodynamic therapy and laser non-linear optical properties (NLO) appropriate for several purposes including optical switching and molecular photoprobe, other arylazo dispersion dyes have also gained considerable interest [14][15][16][17]. β-Enaminones have been used as an important precursors for synthesis of heterocyclic systems [18,19]. In an attempt to establish new precursors, the preparation of which is less expensive than β-enaminones and used in such heterocyclic synthesis, it was considered interesting to examine the synthesis and responces of type β-hydroxyenones, R-CO-CH=CHOH.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of publications devoted to the synthetic methods, chemical transformations, and application of azolopyrimidines indicate the high relevance of this group of compounds. The diversity of the biological properties of azolopyrimidines is explained by their structural similarity to purine bases, which make them capable of interfering in key biochemical processes. Thus, azolopyrimidines have established themselves as antiviral, antibacterial, antidiabetic, antitumor, , and antiglycation agents. Moreover, azolopyrimidines have proved to be a basis for novel organic materials with promising fluorescent properties. …”
Section: Introductionmentioning
confidence: 99%